PENERAPAN MODEL PEMBELAJARAN DISCOVERY INQUIRY TERHADAP PENINGKATAN HASIL BELAJAR IPAS PADA MATERI GAYA DAN GERAK SISWA KELAS IV SD INPRES MINASA UPA - Asmudisar; Aliem Bahri; Nurmiati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to improve student learning outcomes at SD Inpres Minasa Upa, specifically for fourth-grade students. The method used in this research is classroom action research. This study was conducted as an effort to address issues occurring in the classroom. After teaching Natural and Social Sciences (IPAS) with the topic of differences in forces and motion through the Discovery Inquiry method, the results were not as expected because most students struggled to grasp and understand the lesson. This was evidenced by the low exam scores after the learning activities concluded. The reflection identified the cause of this failure: the teacher did not use teaching aids or media during the lessons. Therefore, the researcher initiated this study to improve learning by using real objects as teaching media to enhance student learning outcomes. The research was carried out over two cycles, and by the second cycle, there was noticeable improvement in both student participation in the learning process and their academic performance. Thus, based on the researcher's analysis, teaching using real objects and direct experimentation (Discovery Inquiry) in the IPAS subject on differences in forces and motion can improve the learning outcomes of fourth-grade students at SD Inpres Minasa Upa. This study can also be used by teachers to enhance their creativity and skills in implementing strategies and methods to improve student achievement.